2021
DOI: 10.1037/pro0000390
|View full text |Cite
|
Sign up to set email alerts
|

Piloting a brief intervention to increase positive identity and well-being in transgender and nonbinary individuals.

Abstract: Young adult trans and nonbinary (TNB) individuals have heightened risk of health disparities (Burgwal et al., 2019), mental health concerns (McCann, 2015), severe discrimination (Lelutiu-Weinberger et al., 2020), and attempted suicide in their lifetime (Adams & Vincent, 2019). There are also positive aspects associated with TNB identities (Matsuno & Israel, 2018;Riggle et al., 2011), including authenticity, selfawareness, and connection to community (Riggle et al., 2011;Riggle & Mohr, 2015). Given the context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…In-person interventions also demonstrate improvement in well-being from specific psychosocial activities. For example, exploratory results from a strengths-based pilot study found an increase in participants’ positive identity and well-being after interventions promoting the positive aspects associated with having a TNB identity 151 . In another pilot study, a non-psychotherapy cognitive-behavioural therapy coping skills group intervention significantly reduced depression scores in TNB youth at post-intervention and three months later (although scores remained in the severe range) 192 .…”
Section: Affirming Interventionsmentioning
confidence: 99%
“…In-person interventions also demonstrate improvement in well-being from specific psychosocial activities. For example, exploratory results from a strengths-based pilot study found an increase in participants’ positive identity and well-being after interventions promoting the positive aspects associated with having a TNB identity 151 . In another pilot study, a non-psychotherapy cognitive-behavioural therapy coping skills group intervention significantly reduced depression scores in TNB youth at post-intervention and three months later (although scores remained in the severe range) 192 .…”
Section: Affirming Interventionsmentioning
confidence: 99%
“…The present study tested the effectiveness of using this video as a brief online positive identity intervention to promote well-being in transgender individuals in the Midwest/Southeastern United States. Drawing on reseach that suggests increasing identity-related community connectedness (e.g., Budge et al, 2020; Puckett et al, 2019) and TNB-affirming interventions (e.g., Clements et al, 2021; Craig & Austin, 2016; Knutson et al, 2021) can increase positive outcomes and decrease negative outcomes in TNB individuals, we hypothesized that TNB individuals who watched the video of other TNB individuals sharing their own positive identity narratives would report significantly higher levels of positive transgender identity, PWB, and positive affect, and lower depression and negative affect compared to a control group who watched a general informational video.…”
Section: Positive Tnb Identitymentioning
confidence: 99%
“…Although telehealth services increased during the COVID-19 pandemic (Pinals et al, 2020), TNB people still reported decreased access to gender-affirming resources (Cicero et al, 2020). Given the importance of accessible and effective interventions to support their PWB, we conducted a participatory action project with TNB young adults who created a positive identity video to encourage and support other TNB people (Clements et al, 2021). Participants who created the video reported increased positive identity and higher levels of PWB.…”
Section: Positive Tnb Identitymentioning
confidence: 99%
“…Burdensomeness (negative beliefs and perceptions of being a burden upon others and being incompetent in life) and belongingness (sense of loneliness and disconnection from others) are critical factors in suicidality and especially important to address in TGD people (Joiner, 2005). Studies have found that by supporting and promoting resilience in TGD youth, their well-being is enhanced (e.g., Clements et al, 2021;Snooks & McLauren, 2021;Puckett et al, 2019).…”
mentioning
confidence: 99%